HUBUNGAN DUKUNGAN KELUARGA DENGAN TERJADINYA GANGGUAN KESEHATAN MENTAL PADA PENDERITA HIV/AIDS DI KOTA JAMBI - Sri Putri Handayani (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2022)
Background: People with HIV/AIDS (ODHA) will be vulnerable to the emergence of psychological and social problems, which will then have an impact of mental disorders. One of the factors that influence mental health is family support.Objective: This study aims to analyze the relationship between family support and the occurrence of mental health disorders in HIV/AIDS sufferers.Method: Cross-sectional analytical research using GHQ-12 for mental health analyze andquestionnaire of family support.Result: The results showed that there was relationship between family support and mental healthdisorder (p-value =0,001).Conclusion: Low family support in people with HIV /AIDS will be at risk for experiencing mental health disorders. It is necessary to provide education and outreach to families on how to provide emotional support, instrumental support, appreciation support, and information support for people living with HIV/AIDS.Keywords: Family Support, Mental Health, HIV/AIDS, ODHA.